Ayurved Management of Amyotrophic Lateral Sclerosis (Motor Neuron Disease) (International Journal of Ayurveda and Pharma Research, 2023)
Motor neurons are nerve cells that send electrical output signals to the muscles, affecting the muscles’ ability to function. Motor neuron disease (MND) can appear at any age, but the symptoms usually appear after the age of 50 years. It affects more males than females. The most common type of MND is amyotrophic lateral sclerosis (ALS). A 56-year-old male patient had heaviness and weakness in left lower limb for 4 months. The condition rapidly progressed in the 4 months prior and found difficulty in climbing stairs and swelling in the left foot. Gradually he developed slowness of speech hence consulted allopathic hospital and treated with glutamate blockers, muscle relaxant and physiotherapy. His response to allopathic medications found to be slow. The present case report deals with the case of MND and its Ayurvedic diagnosis and management. Difficulty in differential diagnosis exists between the conditions like Sarvanga Vata, Avrita Vata and Saama Vata. Upashaya- Anupashaya Pariksha is beneficial to solve the problem in differential diagnosis. Swedana and Matra Vasti procedures are found to be beneficial in the management of MND.